Respon Pertumbuhan Gulma dan Hasil Tanaman Jagung terhadap Herbisida 276 G/L pada Sistem Tanam TOT - Uum Umiyati (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2019)
No tillage system (NTS) can save time and cost more efficiently in corn cultivation. The NTS system is closely related to herbicide use. The aimed of this study to study the effect of herbicide paraquat dichloride 276 g / L in suppressing weed growth in hybrid corn plantations with NTS. The study was conducted in April-September 2017 on land located in Tenjolayar Village, Cigasong District, Majalengka with an altitude at 193 above the sea level. The experiments used Randomized Complately Block Design (RCBD) with 6 treatments and 4 replications so there’re 24 experimental plots. The treatment were 1) 0.75 L / ha + TOT, 2) 1 L / ha + TOT, 3) 1.25 L / ha + TOT, 4) 1.5 L / ha + TOT, 5) Weeding manual + TOT, and 6) Control (OTS). Differences between treatments were tested using the F test, while to test the average value of treatment used Duncan's Multiple Distance Test 5%. Herbicide paraquat dichloride 276 g / L affects could suppress weed growth done on 1 week after application and 5 weeks after application. The optimum dose of paraquat dichlorthereide 276 g / L in weed control in hybrid corn plantations was 1.5 L / ha at 1 week after application and 5 weeks after application.